Managing resources - Martin, G.J.; Barrow, S.; Cunningham, A.B.; Shanley, P. (UNESCO/WWF/Kew, 2001)
The People and plants handbook is a source of information on applying ethnobotany to conservation and community development. It is designed for people who work in the field, including park managers, foresters, students, researchers, cultural promoters, and members of non-governmental, governmental and indigenous organizations.